2009
DOI: 10.4284/sej.2009.76.2.533
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High School JROTC on Student Achievement, Educational Attainment, and Enlistment

Abstract: The Junior Reserve Officers' Training Corps (JROTC) is a high school initiative that serves many at-risk students. Its goals range from reducing dropout rates and improving academic achievement to preparing students for military careers. Using data from High School and Beyond (HSB) and the National Educational Longitudinal Study (NELS), we estimate average treatment effects on students attending schools that typically host JROTC. Applying a twostage matching technique, we find that JROTC participants have poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…Two studies (Pema and Mehay, 2009a;Biggs, 2010) found a positive correlation between JROTC and enlistment. One study found a positive correlation only for students who enrolled in JROTC early in high school and persisted in the program through senior year (Pema and Mehay, 2009b).…”
Section: Nonacademic Benefitsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies (Pema and Mehay, 2009a;Biggs, 2010) found a positive correlation between JROTC and enlistment. One study found a positive correlation only for students who enrolled in JROTC early in high school and persisted in the program through senior year (Pema and Mehay, 2009b).…”
Section: Nonacademic Benefitsmentioning
confidence: 99%
“…Two studies (Pema and Mehay, 2009a;Biggs, 2010) found a positive correlation between JROTC and enlistment. One study found a positive correlation only for students who enrolled in JROTC early in high school and persisted in the program through senior year (Pema and Mehay, 2009b). Another study found that the impact of JROTC participation on military enlistment decisions is negligible when self-selection into the JROTC program is accounted for (Days and Ang, 2004).…”
Section: Nonacademic Benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are also more likely to transfer to a higher-level college and to complete a bachelor's degree. Using an randomized experiment design, Scrivener et al, 2008, analyze the effects of learning communities, which placed college freshmen in groups of up to 25 who took three classes 5 Using quasi-experimental methods, Pema and Mehay, 2009, study the impact of the Junior Reserve Officers' Training Corps (JROTC), a program that combines classroom instruction, with more broad extra-curriculum activities-such as physical education, military drill and customs, community service activities, and summer camp. The evidence of the program on high-school students' education and labour market outcomes is mixed.…”
Section: B Empirical Evidencementioning
confidence: 99%